Integration of transanal techniques for precise rectal transection and single‐stapled anastomosis: a proof of concept study. (8th May 2019) - Spinelli, A.; Carvello, M.; D'Hoore, A.; Foppa, C.
Abstract: Aim: Transection of the distal rectum and subsequent anastomosis differ between the open, minimally invasive and transanal approaches. With the transanal technique, there is direct control of the transection level and the single‐stapled anastomosis, thus overcoming two crucial limitations of rectal surgery. This study describes a technique for precise a transanal rectal transection with a single‐stapled (TTSS) colorectal, coloanal or ileoanal anastomosis in 20 consecutive patients undergoing low rectal surgery. Methods: After completing rectal dissection by the preferred technique (open or minimally invasive), TTSS was created. The detailed video describes this technique. Results: TTSS was feasible in all patients: 13 underwent total mesorectal excision + TTSS for low rectal cancer and seven underwent ileoanal pouch + TTSS for benign disease. Complications included one Grade IIIa and three Grade I, according to the Clavien–Dindo classification (median follow‐up 6 months). Conclusion: TTSS represents a technique which can be applied regardless of the preferred approach (open, minimally invasive or transanal) for low rectal dissection. The adoption of TTSS could well allow for a more consistent comparison of the outcomes following the differing approaches to rectal surgery.